Electric automobile integrated power system and electric automobile - WANG SHUNJUN (2015)
The utility model discloses an electric automobile integrated power system and an electric automobile. The system comprises a drive motor controller, a generator controller, a power-assisted steering motor controller, a brake pump motor controller and a DC-DC power module and further comprises a power management module and a high-voltage power distribution module. The power management module, the high-voltage power distribution module, the drive motor controller, the generator controller, the power-assisted steering motor controller, the brake pump motor controller and the DC-DC power module are connected to an internal CAN bus, and the power management module is connected with a whole automobile controller through an external CAN bus. Unified managing and monitoring on all subcomponents can be achieved through data receiving and transmitting achieved through the CAN buses, and therefore the power management module, the high-voltage power distribution module and all the subcomponents can be integrated, the functions are complete, the product size is small, and the power density is high.